PREVALENCE OF THE RESPIRATORY SYNCYTIAL VIRUS INFECTION IN THE WINTER AND SPRING MONTHS AMONG BULGARIAN CHILDREN YOUNGERTHAN 2 YEARS OF AGE - E.Kostadinova; S.Angelova (Trakia Journal of Sciences)
Lower respiratory tract infections (LRTIs) in children from 2 months to 5 years of age are significant for clinical practice and researchers because of their high incidence, risk of severe clinical course, and development of chronic complications. About 60% of LRTIs are caused by viral infections. PURPOSE: To make an etiological diagnosis of viral infections of the lower respiratory tract-acute bronchiolitis and viral pneumonia. To present an epidemiological characterization in relation to the identified viral agents. METODS:The subjects of the prospective study were 101 children aged 2 months to 5 years, hospitalized in the Clinic of Pediatrics with clinical manifestations of viral LRTI`s with bronchial obstruction. Clinical material was analyzed according to the main epidemiological parameters: sex, age, place of residence, season, etiological agent of infection, etiological diagnosis according to season, presence of risk factors from family history and comorbidities. Etiological diagnosis of viral LRTIswas made by RT-PCR analysis. RESULTS: Epidemiological characteristics of the diagnosed viral LRTIs are presented. The prevalence of male sex was found to be higher (without statistical significance), more frequent amongurban children and the highest incidence of viral LRTIs in the age up to 2 years. The etiological diagnosis made shows that respiratory syncytial virus (RSV) is the most common etiological cause of acute bronchiolitis in children under 2 years of age, both alone and in co-infections.CONCLUSIONS:RSV is the most common statistically significant etiological cause in winter and spring. Rhinovirus (RV) is the leading etiological cause in summer and autumn. Co-infections involving RSV and RV also have a highincidence during these seasons.